2019
DOI: 10.1111/imj.14391
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of hip fracture and vitamin D deficiency persists in a sub‐tropical climate

Abstract: Both hip fractures and vitamin D (25‐hydroxyvitamin D (25‐OHD)) deficiency are more common in winter in regions with temperate climates, but few data exist for a sub‐tropical climate. In a South East Queensland tertiary hospital over a 7‐year period, there were significantly more hip fractures in winter than the other three seasons (analysis of variance P = 0.003), with associated higher frequency of 25‐OHD deficiency – 42.5% in winter compared to 28.5% in summer, odds ratio 1.86 (95% confidence interval 1.35–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
6
1
2
Order By: Relevance
“…Notably, our finding of the positive association between warmer weather and injurious falls contrasts with other work reporting a higher risk of fall-related injuries in winter or colder seasons in both northern and southern hemispheres, possibly attributed to slipping on ice or snow [ 12 , 13 , 15 , 16 ]. One key difference is that these studies defined injury as a fracture, of which cases were often detected through medical records, while the present study emphasized all injuries, including bruising or pain, as reported via a monthly calendar.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Notably, our finding of the positive association between warmer weather and injurious falls contrasts with other work reporting a higher risk of fall-related injuries in winter or colder seasons in both northern and southern hemispheres, possibly attributed to slipping on ice or snow [ 12 , 13 , 15 , 16 ]. One key difference is that these studies defined injury as a fracture, of which cases were often detected through medical records, while the present study emphasized all injuries, including bruising or pain, as reported via a monthly calendar.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, understanding periods of the year associated with a higher risk for falling and lower levels of physical activity could guide individuals on how to preserve physical activity and prevent falls throughout the year. Prior work has suggested a relationship between weather and seasons with falls, fall-related injuries [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], and physical activity [ 18 , 19 , 20 , 21 , 22 , 23 ]. However, literature describing how falls and physical activity vary across weather conditions and seasons is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of vitamin D deficiency is much higher in winter and spring than in summer and autumn, and there is evidence that the incidence of hip fracture is also higher in winter (24,25) . Our analyses do not account for season, as the hospital morbidity data do not present data stratified by season, but the proportion of winter hip fractures and falls hospitalisations attributable to vitamin D deficiency may be greater than that estimated here.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with hip fracture displayed lower calcium and increased alkaline phosphatase, which might signal presence of more osteomalaica in the hip fracture cohort. As several previous studies have demonstrated much lower vitamin D levels in hip fracture patients [2,[26][27]. The relationship between the serum levels of TMAO, vitamin D and hip fracture need to be elaborated in future research.…”
Section: Agingmentioning
confidence: 92%